Spaniards behind Barbed Wire. Republicans in the French, Nazi and Soviet camps (1939-1956) - Iordache Cârstea, Luiza (Hispania Nova, 2019)
In a common destiny, many Spanish Republicans were victims of policies of rejection, exclusion, persecution, violence and punishment as «undesirable» foreigners, «opponents», «reds», «enemies» or candidates to be in democratic regimes and «totalitarian» ones, specifically in the Third French Republic, Nazi Germany and the USSR under Stalin. As a result of these policies, besides the European circumstances and the political, social and economic context of those countries, thousand and thousand Spaniards were interned, deported and detained in French, Nazi and Soviet camps. Based on the shared experience of exile and internment, the article analyzes the vía crucis of the Spaniards in those concentracionary systems and reflects the common and unique characteristics of those from a comparative approach.
Keywords: Exile; concentration camps; France; Third Reich; USSR